Heparin: Induced thrombocytopenia: Incidence and laboratory approach to diagnosis in Indians - Jyoti Kotwal; Sanjeev Chaudhary; Madakshira Gopal Manoj; Shahbaz Hasnain; Velu Nair; Manoj Luthra (Wolters Kluwer Medknow Publications, 2014)
Background and objectives: One of the most common complications of heparin administration is heparin-induced thrombocytopenia (HIT) which can also lead to catastrophic thrombotic events. The problem of identifying the cause of thrombocytopenia, as due to heparin, in patients with multiple co-morbid conditions is very essential for management. Thus, the laboratory investigations for diagnosis of HIT play a pivotal role. The objective of the study was to arrive at the incidence of HIT in ethnic Indian population and provide a decision after analysis of tests used to diagnose HIT. Materials and Methods: 125 consecutive patients (Power of study being 80%) undergoing open heart surgery and receiving unfractionated heparin were taken as subjects. Blood samples were collected a day before the surgery and days 1, 3, 5 and 7 after surgery. The cases were categorized into probable and unlikely groups depending on the clinical presentation and degree fall of platelet count. Anti-heparin PF4-associated antibodies were detected using rapid-ID gel microtyping system and ELISA tests. HIT was also tested using functional assays:- heparin-induced platelet aggregation test (PAT) and the rapid luminographic assay of heparin-induced ATP release. Results: Of the 125 patients, 11 patients were clinically labeled as probable HIT and 29 patients were clinically labeled as unlikely HIT. There were seven confirmed cases of HIT cases that were positive for one functional and one immunological assay. Only one case of HITT was encountered. Accordingly, the incidence of HIT was found to be 5.6 % and that of HITT to be 0.8%. ELISA tests were positive in 21 cases (17%) which demonstrated the presence of anti-HPF4 antibodies in non-HIT cases as well. It was found that the rapid gel test had sensitivity comparable to functional assay with better specificity than ELISA. Interpretation and conclusions: Incidence of HIT in ethnic Indian population is 5.6%. Patients with a drop of >50% in platelet count should be perused as a likely candidate of HIT. These cases should be subjected to the ID-HPF4 antibody assay as this is a rapid test, can be done for individual cases, and has better specificity and similar sensitivity than ELSIA. Cases with clinically probable HIT and a positive ID-HPF4 assay can be taken as confirmed cases of HIT. However, cases clinically unlikely for HIT and a positive ID-HPF4 assay should be subjected to another test to establish the diagnosis of HIT.